Pancancer analysis of the prognostic and immunological role of FANCD2: a potential target for carcinogenesis and survival - Zedan Zhao; Ruyu Wang; Ruixue Wang; Jialing Song; Fengjun Ma; Huafeng Pan; Cuiyun Gao; Deqiang Wang; Xuemei Chen; Xiangzhen Fan (BMC Medical Genomics, 2024)
Abstract Recent evidence has shed light on the significant role of FANCD2 in cancer initiation, development, and progression. However, a comprehensive pan-cancer analysis of FANCD2 has been lacking. In this study, we have conducted a thorough investigation into the expression profiles and prognostic significance of FANCD2, as well as its correlation with clinicopathological parameters and immune cell infiltration, using advanced bioinformatic techniques. The results demonstrate that FANCD2 is significantly upregulated in various common cancers and is associated with prognosis. Notably, higher expression levels of FANCD2 are linked to poor overall survival, as indicated by Cox regression and Kaplan-Meier analyses. Additionally, we have observed a decrease in the methylation of FANCD2 DNA in some cancers, and this decrease is inversely correlated with FANCD2 expression. Genetic alterations in FANCD2 predominantly manifest as mutations, which are associated with overall survival, disease-specific survival, disease-free survival, and progression-free survival in certain tumor types. Moreover, FANCD2 exhibits a strong correlation with infiltrating cell levels, immune checkpoint genes, tumor mutation burden (TMB), and microsatellite instability (MSI). Enrichment analysis further highlights the potential impact of FANCD2 on Fanconi anemia (FA) pathway and cell cycle regulation. Through this comprehensive pan-cancer analysis, we have gained a deeper understanding of the functions of FANCD2 in oncogenesis and metastasis across different types of cancer.